Vertical Zika Virus Transmission at the Maternal-Fetal Interface - Guzeloglu-Kayisli, Ozlem; Kayisli, Umit Ali; Schatz, Frederick; Lockwood, Charles Joseph (Frontiers in Virology, 2022)
Zika virus (ZIKV) is spread by mosquito bites or via sexual or vertical transmission. ZIKV-infected adults are generally asymptomatic, but can display mild symptoms including fever, joint pain, rash, and conjunctivitis. However, during pregnancy, vertical ZIKV transmission can cause placental dysfunction and result in severe fetal defects, including microcephaly, retinopathy, fetal growth restriction and/or stillbirth. Since no vaccine or anti-viral agents approved by the FDA are currently available, ZIKV infection poses a major global maternal-fetal health challenge. The maternal-fetal interface includes maternal decidual stromal and immune cells and fetal-derived extravillous trophoblasts. Syncytiotrophoblasts, which form the outer layer of floating villi, are non-permissive to ZIKV, thereby preventing transmission of ZIVK to the underlying cytotrophoblasts and/or other cells such as fetal endothelium in these villi. However, anchoring villi are tightly attached to the decidua and their cytotrophoblastic cell columns are ZIKV-permissive, suggesting this location as the most likely site of ZIKV vertical transmission. Therefore, at the maternal-fetal interface, decidual cells likely serve as a reservoir of ZIKV persistence since they: 1) overexpress viral entry molecules compared to trophoblasts; 2) are highly permissive to ZIKV infection in a gestational age-dependent manner (more easily infected earlier in gestation); 3) augment ZIKV infection of weakly permissive primary cytotrophoblast cultures; and 4) display local maternal-immune tolerance, which prolongs ZIKV survival to facilitate maternal-fetal transmission. This review focuses on molecular mechanisms underlying ZIKV infection of cells at the maternal-fetal interface, highlighting how decidual cells enhance propagation of ZIKV in extravillous cytotrophoblasts and why development of agents that eliminate ZIKV persistence in reproductive tissues before pregnancy is crucial to prevent perinatal ZIKV transmission.